Uneven Adoption of Artificial Intelligence Tools Among U.S. Teachers and Principals in the 2023–2024 School Year - Kaufman, Julia H.; Woo, Ashley; Eagan, Joshua; Lee, Sabrina; Kassan, Emma B. (RAND Corporation, 2025)
Drawing on nationally representative survey data, the authors examine the use of artificial intelligence (AI) tools and products among teachers and principals and the presence of school policies on the use of AI during the 2023–2024 school year. Their findings provide useful information for those who support teachers at the school, district, and state levels, as well as providers and developers of AI tools for use by teachers and students.
Keywords: Alumni; Artificial Intelligence; Education Curriculum; Educational Technology; Principals; Research; Students; Teachers and Teaching